Substance abuse, dragging into crime, mental health disorders and nursing care in child and adolescents - Baysan Arabacı, Leyla; Taş, Gülsenay; Dikeç, Gül (Journal of Dependence, 2017)
According to the Universal Declaration of the Rights of the Child, every individual who is between the ages of 0 and 18 is considered to be a child and in this period risky behaviors, disruptions or traumas have a role in the development of psychiatric disorders. Children and adolescents who are exposed to risky behaviors can be dragged into criminal behavior by many factors. Studies show that delinquent and substance abuse behaviors are seen together and that the frequency is increasing steadily. The frequency of mental illness is also high in child-adolescents who are admitted to the mental health clinics with substance use and delinquent behavior story. At this point, psychiatric nurses who care for the childadolescents that admitted to the clinic should consider this specific situation of the child. From this point of view, the aim of this review is to give information about possible psychiatric problems seen in childadolescents who have drug use and delinquent behavior and possible nursing care for these problems...